2020
DOI: 10.1038/s41598-020-70390-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide administration for a mouse model of cerebellar ataxia with neuroinflammation

Abstract: Most cerebellar ataxias (cAs) are incurable neurological disorders, resulting in a lack of voluntary control by inflamed or damaged cerebellum. Although CA can be either directly or indirectly related to cerebellar inflammation, there is no suitable animal model of CA with neuroinflammation. In this study, we evaluated the utility of an intracerebellar injection of lipopolysaccharide (LpS) to generate an animal model of inflammatory CA. We observed that LPS administration induced the expression of pro-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
1
16
1
Order By: Relevance
“…To investigate the potential effects of hMSCs against neuroinflammation in the cerebellum of ICA mice, we examined whether the treatment with hMSCs inhibited LPS-induced glial activation 7 days after hMSC transplantation, which was the time point indicated by the inflammatory responses following LPS treatment [ 14 ]. As shown in Figure 3 C, LPS-induced microglial activation was inhibited by hMSC treatment in a dose-dependent manner, whereas reactive astrocytes were not affected by hMSC treatment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To investigate the potential effects of hMSCs against neuroinflammation in the cerebellum of ICA mice, we examined whether the treatment with hMSCs inhibited LPS-induced glial activation 7 days after hMSC transplantation, which was the time point indicated by the inflammatory responses following LPS treatment [ 14 ]. As shown in Figure 3 C, LPS-induced microglial activation was inhibited by hMSC treatment in a dose-dependent manner, whereas reactive astrocytes were not affected by hMSC treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no previous study of the effects of MSCs in an animal model of CA associated with neuroinflammation. To assess the therapeutic effects of hMSCs on inflammatory CAs (ICA), we used ICA mice, which were developed in our previous study [ 14 ]. A previous study of ICA mice showed that balance and motor control disabilities, indicating cerebellar dysfunction, were accompanied by the upregulation of proinflammatory molecules via glial activation and followed by apoptotic Purkinje cell loss.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations